Investigation on the tribological behaviour of modified jatropha oil with hexagonal boron nitride particles as a metalworking fluid for machining process - Talib, Norfazillah; Md. Nasir, Ramdziah; Abd. Rahim, Erween (Penerbit UTHM, 2018)
Bio-based oil from vegetable oils was recently explored as an alternative solution to petroleum-based oil. However, the application of vegetable oils as metalworking fluids (MWFs) for machining process is still not widespread. The objective of this study was to investigate the tribological behaviour of modified vegetable oils, in comparison with synthetic ester (SE) and crude jatropha oil (CJO). In this study, the CJO was chemically modified via transesterification process to develop modified jatropha oil (MJO5). MJO5 was then blended with the hexagonal boron nitride (hBN) particles at various concentrations ranging between 0.05 to 0.5wt.%. The friction and wear test was performed using four ball tribotester. An experiment on orthogonal cutting process was carried out to evaluate the machining performances in terms of cutting force, cutting temperature, chip thickness and toolchip contact length. The results reveal that the mixture of 0.05wt.% of hBN particles in the MJO5-based oil (MJO5a) outperformed the SE in terms of friction and wear. MJO5a showed excellent machining performances by reducing the machining force and temperature, which related to the formation of thinner chips and small tool-chip contact length. MJO5a is the best substitute to SE as sustainable MWFs in the machining operation with regards to the environmental and health concern.